AMPK-α1 or AMPK-α2 Deletion in Smooth Muscles Does Not Affect the Hypoxic Ventilatory Response or Systemic Arterial Blood Pressure Regulation During Hypoxia - MacMillan, Sandy; Evans, A. Mark (Frontiers in Physiology, 2018)
The hypoxic ventilatory response (HVR) is markedly attenuated by AMPK-α1 deletion conditional on the expression of Cre-recombinase in tyrosine hydroxylase (TH) expressing cells, precipitating marked increases in apnea frequency and duration. It was concluded that ventilatory dysfunction caused by AMPK deficiency was driven by neurogenic mechanisms. However, TH is transiently expressed in other cell types during development, and it is evident that central respiratory depression can also be triggered by myogenic mechanisms that impact blood supply to the brain. We therefore assessed the effect on the HVR and systemic arterial blood pressure of AMPK deletion in vascular smooth muscles. There was no difference in minute ventilation during normoxia. However, increases in minute ventilation during severe hypoxia (8% O2) were, if affected at all, augmented by AMPK-α1 or AMPK-α2 deletion in smooth muscles; despite the fact that hypoxia (8% O2) evoked falls in arterial SpO2 comparable with controls. Surprisingly, these mice exhibited no difference in systolic, diastolic or mean arterial blood pressure during normoxia or hypoxia. We conclude that neither AMPK-α1 nor AMPK-α2 are required in smooth muscle for the regulation of systemic arterial blood pressure during hypoxia, and that AMPK-α1 deficiency does not impact the hypoxic ventilatory response by myogenic mechanisms.